The Latest Developments in Immunomodulation of Mesenchymal Stem Cells in the Treatment of Intrauterine Adhesions, Both Allogeneic and Autologous - Chen, Jia-ming; Huang, Qiao-yi; Zhao, Yun-xia; Chen, Wei-hong; Lin, Shu; Shi, Qi-yang (Frontiers in Immunology, 2021)
Intrauterine adhesion (IUA) is an endometrial fibrosis disease caused by repeated operations of the uterus and is a common cause of female infertility. In recent years, treatment using mesenchymal stem cells (MSCs) has been proposed by many researchers and is now widely used in clinics because of the low immunogenicity of MSCs. It is believed that allogeneic MSCs can be used to treat IUA because MSCs express only low levels of MHC class I molecules and no MHC class II or co-stimulatory molecules. However, many scholars still believe that the use of allogeneic MSCs to treat IUA may lead to immune rejection. Compared with allogeneic MSCs, autologous MSCs are safer, more ethical, and can better adapt to the body. Here, we review recently published articles on the immunomodulation of allogeneic and autologous MSCs in IUA therapy, with the aim of proving that the use of autologous MSCs can reduce the possibility of immune rejection in the treatment of IUAs.